2011
DOI: 10.1021/jf203742x
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Resolution and Growth-Retardant Activity in Rice Seedlings of Uniconazole

Abstract: The increasing application of chiral pesticides has enhanced interest in their enantioselectivity. However, little relevant information is currently available for enantioselective activity of chiral plant growth regulators. In an attempt to screen active enantiomers of uniconazole, this work investigated enantiomeric separation and the enantioselective effect of uniconazole on the growth of rice seedlings and cyanobacteria. Baseline resolution of uniconazole enantiomers was achieved on a Chiralpak AD column by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Studies have shown that the introduction of different functional groups is a strategy used to improve the biological activity. The influence of structures on antifungal activities is useful for guiding synthesis and screening the most promising potent broad spectrum antifungal compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the introduction of different functional groups is a strategy used to improve the biological activity. The influence of structures on antifungal activities is useful for guiding synthesis and screening the most promising potent broad spectrum antifungal compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking with the highest score was chosen for further analysis. 16,17 3 | RESULTS AND DISCUSSION…”
Section: Separation Mechanisms and Molecular Docking Studiesmentioning
confidence: 99%
“…Heterocycles bearing a 1,2,4‐triazoles moiety have several applications in organocatalysts, medicines, and pesticides . Moreover, thiazolo[3,2‐b] [1,2,4]triazoles nucleus has been the subject of intense interest because of its remarkable biological properties …”
Section: Introductionmentioning
confidence: 99%